Shadow of the Titanic : the extraordinary stories of those who survived - Wilson, Andrew, 1967- (Atria Books, 2012)
We think we know the story of the Titanic<U+2014>the once majestic and supposedly unsinkable ship that struck an iceberg on its maiden voyage from Britain to America<U+2014>but very little has been written about the vessel<U+2019>s 705 survivors. How did the events of that horrific night in the icy waters of the North Atlantic affect the lives of those who lived to tell the tale? Drawing on a wealth of previously unpublished letters, memoirs, diaries, and interviews with their family members, award-winning journalist Andrew Wilson brings to life the survivors<U+2019> colorful voices, from the famous, like heiress Madeleine Astor, to the lesser known second-and third-class passengers, such as the Navratil brothers, who were traveling under assumed names because they were being abducted by their father.